Dissociation, identity distress and rejection sensitivity in adult adoptees. (July 2022) - McLamb, Lee J; Wagaman, Bailey; Kerr, Emalee; Berman, Steven L
This US study examined dissociation, rejection sensitivity and identity distress among adults who experienced adoption as a child and the relationship between these factors. Further, groups of adoptees recruited through Amazon Mechanical Turk (MTurk) and social media were compared to assess whether these two recruitment methods achieve similar results. Adopted adults ( n  = 389) and non-adopted adults ( n  = 151) completed an online survey. Significant differences were found between adopted and non-adopted groups on the measures of dissociation, rejection sensitivity and identity. Rejection sensitivity and dissociation were also found to be better predictors of identity problems than adoption status alone. Recruitment methods resulted in significant differences on measures. Implications for consideration in a clinical setting are discussed as well as potential areas for future research.